Complete structure and organization of immunoglobulin heavy chain constant region genes in a phylogenetically primitive vertebrate. - Kokubu, F (1988)
Immunoglobulin (Ig) gene organization in Heterodontus francisci (horned shark), a phylogenetically primitive vertebrate, is unique. Homologous Ig heavy chain variable (VH) and constant region (CH) specific probes were used to screen a spleen cDNA library constructed in lambda gt11. Both secretory (SEC) and transmembrane (TM) cDNA clones were recovered; the latter were identified by a negative selection strategy. The complete sequence of the CH portion of a Heterodontus genomic DNA-lambda clone also was determined. The sequences of the individual CH genes differ from each other in all exons. When compared to mammalian prototypes, similarities in exon and intron organization as well as conservation of sequences involved with differential splicing of SEC and TM mRNA indicate that Heterodontus heavy chain genes are of the mu type, although intron lengths are uniformly longer in Heterodontus. Heterodontus genes are not associated, however, with the family of DNA sequences that have been implicated in heavy chain class switching in mammals. Spleen cDNA library screening and RNA blot analyses indicate that mRNAs encoding TM Ig are exceedingly rare. The relationship between this quantitative difference and the distribution of polyadenylation signal sequences suggests that regulation of Ig gene expression in Heterodontus may be highly dependent on position effects.